Children and Contact Lenses: Where Do They Fit into the Spectrum of Care? - Newman, Christina (Journal of Behavioral Optometry, 2012)
Many improvements have been made by the contact lens industry in the past decade. Eye care providers should take a fresh look at the use of contact lenses as part of their vision correction plan for the pediatric population. It is not uncommon for practitioners to tell parents that their child cannot be fitted into contact lenses until at least 13 years of age. Recent studies are proving that children are at no additional health risk, are just as satisfied, and are as capable of caring for their lenses as compared to teens. Children and teens benefit equally in selfperception and confidence in terms of appearance and correction during their given activities. Beyond normal vision correction, contact lenses are also being examined for their ability to halt the progression of myopia, as well as their role in correction of infant aphakia. The following article provides a review of the latest findings and attitudes for fitting children into contact lenses.